Community Empowerment through Dasawisma and Household Quality of Life within the Enabling–Empowering–Protecting Framework - Jordy Smith Rabuka; Selvi Diana Meilinda (Jurnal Pemberdayaan Masyarakat, 2026)
The family is the smallest level at which human development in Indonesia remains inadequate. When the responsibilities of each family member are well-fulfilled, and a sound management system supports the household's quality of life, family welfare can be considered good. For human development to succeed, men, especially heads of households, must actively participate in providing for the family's basic needs. Due to Indonesia's patrilineal cultural framework, women are underrepresented in human development initiatives. Consequently, Dasawisma (village-based community development programs) serves as a means of empowering women to improve household living standards. The purpose of this study was to determine whether the quality of life of urban households through Dasawisma can improve overall human development in Wenang District, Manado City. Data were collected directly from respondents using standardized instruments as part of a quantitative approach utilizing explanatory research. The results of statistical findings show in the t-Test that the Protecting variable (X3) is greater than the Enabling (X1) and Empowering (X2) variables so that it is the most dominant among the three and significant for household quality, this is also in line with the positive regression coefficient which shows that the higher the role of Protecting (X3) felt by the household, the higher the quality of life achieved.